Distribution of Energy Density and Optimization on the Surface of the Receiver for Parabolic Trough Solar Concentrator - Fei Chen; Ming Li; Peng Zhang (International Journal of Photoenergy)
The geometrical optics model about the offset effect of solar rays by the thickness of concentrating mirror and the diametric solar model were established. The radiant flux density on the surface of the receiver for parabolic trough solar concentrator was obtained by numerical calculation with the established models. Charge-coupled device (CCD) was used for testing gray image on the surface of the receiver for parabolic trough solar concentrator. The image was analyzed by Matlab and the radiant flux density on the surface of the receiver for parabolic trough solar concentrator was achieved. It was found that the result of the theory is consistent with that of the experiment, and the relative deviation on the focal length width was 8.7%. The geometrical structure of receiver based on parabolic trough solar concentrator was optimized, a new parabolic receiver has been proposed, and it has been shown that the optimized geometrical structure of receiver was beneficial to improve the working performance of the entire system.